Kesiapan Siswi Sekolah Dasar Dalam Menghadapi Menarche - Angelina Kadek Windy Artika; Ni Luh Agustini Purnama; Yuni Kurniawaty (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:    To identify the level of readiness of elementary school students when facing the first menstruation (menarche)Methods:   The design of this research is a descriptive study through the use of data collection techniques, namely saturated sampling or total sampling. In this study, the variable is the level of readiness of elementary school students in facing the first menstruation (menarche). In The sample used was 36 respondents, they were who met the inclusion criteria that was 3rd grade elementary school students (aged 9-10 years), had not experienced menstruation, and were willing to be respondents. A questionnaire about the readiness of elementary school students to face menarche was used as an instrument in this study Results:   Descriptive Statistical Analysis showed that 80% of respondents were not ready to face menarche and 20% of respondents were ready to face menarcheConclusion:  Most elementary school students are not ready to face menarche because they have not received information about menstruation